Effects of modified binders obtained from different polymers on conventional and rheological properties - Yalcin, Erkut; Demirbag, Abdullah (Elsevier Sci Ltd, 2022)
For the bituminous hot mix layers to resist the increased traffic load and number for a long time without deforming, binders modified with the Styrene-Butadiene-Styrene (SBS) polymer additive are commonly used in the asphalt material. The high demand for SBS makes its delivery difficult when needed and thus the use of alternative additives has been discussed. In this study, three different polymers (701, 611, and SBS) were compared. The effect of the bituminous binder on its physical, chemical, and rheological properties was examined. Conventional (force ductility, penetration, viscosity, softening point tests, etc.) and Superpave binder (bending beam rheometer and dynamic shear rheometer) tests were performed on pure and modified binders. Additionally, Fourier-transform Infrared Spectroscopy (FTIR) test was done on aged modified binder specimens. As a result, the conventional and Superpave binder test results of 4 different binders showed that the binders increased the performance levels of the pure binder. Furthermore, the results of the tests proved that 701 and 611 polymers could be used instead of SBS polymers. In particular, it was found that the rutting performance of the 611 polymer was better than other polymers.
Keywords: Modified asphalt; Rheology; SBS; 701 Polymer; 611 Polymer